Recent developments and highlights in biomarkers in allergic diseases and asthma. Issue 12 (30th October 2018) - Eguiluz‐Gracia, Ibon; Tay, Tunn Ren; Hew, Mark; Escribese, Maria M.; Barber, Domingo; O'Hehir, Robyn E.; Torres, Maria J.
Abstract: The potential of precision medicine in allergy and asthma has only started to be explored. A significant clarification in the pathophysiology of rhinitis, chronic rhinosinusitis, asthma, food allergy and drug hypersensitivity was made in the last decade. This improved understanding led to a better classification of the distinct phenotypes and to the discovery of new drugs such as biologicals, targeting phenotype‐specific mechanisms. Nevertheless, many conditions remain poorly understood such as non‐eosinophilic airway diseases or non‐IgE–mediated food allergy. Moreover, there is a need to predict the response to specific therapies and the outcome of drug and food provocations. The identification of patients at risk of progression towards severity is also an unmet need in order to establish adequate preventive or therapeutic measures. The implementation of precision medicine in the clinical practice requires the identification of phenotype‐specific markers measurable in biological matrices. To become useful, these biomarkers need to be quantifiable by reliable systems, and in samples obtained in an easy, rapid and cost‐efficient way. In the last years, significant research resources have been put in the identification of valid biomarkers for asthma and allergic diseases. This review summarizes these recent advances with focus on the biomarkers with higher clinical applicability.